Assessment of variance in measurement of hectolitre mass of wheat and maize, using equipment from different grain producing and exporting countries - Engelbrecht, Mandy L. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2008.